Nearest neighbor queries in spatial database - Liu, Danzhou. (2008)
In this thesis, we propose a k-Nearest Neighbor query processing algorithm that uses one or more window query to retrieve the nearest neighbors of a given query point. We also propose three different methods to estimate the ranges to be used by the window queries. Each range estimation method requires different statistical knowledge about the spatial database.